Social Assessment and the Baku Water Supply Project - World Bank (World Bank, Washington, DC, 2012)
The World Bank supports development that improves human welfare and reduces poverty. Achieving this goal requires sustainable economic growth; the development of physical infrastructure, human resources, and institutions; and sound environmental management. In recent years development practitioners have recognized that having stakeholders participate in project selection and design has a number of advantages: it can help reach the poor and other vulnerable groups, strengthen participants' "ownership" of the project, and improve decision-making. Development practitioners also recognize that systematic social analysis can help ensure that projects achieve their objectives, that they are appropriately targeted, that they are acceptable to the intended beneficiaries, and that they are institutionally feasible. Social assessment (SA) supports participation, and is a tool for incorporating social analysis into the Bank's projects and analytical work. SA is the systematic investigation of the social processes and factors that affect the outcomes of development projects. In project work, Bank staff use SA to identify key stakeholders and establish a framework for their participation in the project, to ensure that intended beneficiaries find the project's objectives acceptable, to assess the social impacts of a project and determine how to mitigate any adverse impacts, and to develop the institutional capacity necessary for the project to succeed.